THE INFLUENCE OF CELEBRITY ENDORSERS AND BRAND TRUST ON CONSUMER PURCHASING DECISIONS ON THE ORIGINAL SKINCARE PRODUCTS IN TANA TORAJA - Lolopayung1, Charisma; Batara Marewa, Jens; Rundupadang, Helba (Universitas Islam Lamongan, 2024)
The purpose of this study was to determine the effect of Celebrity Endorser and Brand Trust on consumer purchasing decisions on The Originote skincare products in Tana Toraja partially and simultaneously. The data collection procedure for this study is: questionnaire. The method used in this study is the Quantitative Method using the Multiple Linear Regression method and processed using SPSS 29. This study was conducted in Tana Toraja Regency, with a sample of 97 respondents. The technique used by researchers in sampling is the Lemeshow formula. The results of the calculation with the t test on the Celebrity Endorser variable t count> t table with a value of (8.137)> (1.661) and on the Brand Trust variable t count> t table with a value of (6.572)> (1.661). The conclusion of this study is that Celebrity Endorser and Brand Trust influence Consumer Purchasing Decisions on The Originote Skincare Products in Tana Toraja partially and simultaneously.